(untitled) (Plant Tissue Culture and Biotechnology, 2019)
An efficient and reproducible in vitro regeneration protocol was established for two varieties of ginger (Z. officinale Roscoe) namely, BARI Ada-1 and Chinese ginger accession number SG876). In case of BARI Ada-1 best result was obtained on MS supplemented with 2.0 mg/l BAP, 0.5 mg/l Kn and 0.5 mg/l NAA. In this combination, 95% rhizome bud explants responded within 6 - 8 days and mean number of shoots per explant was 8.79 ± 0.42. On the other hand, Chinese ginger showed best (90%) shoot regeneration response from the same explants on the same medium and hormonal combinations but in exchange of 0.25 mg/l NAA. In this hormonal composition shoot initiation started within 7 - 8 days of culture and mean number of shoots/explant was 6.83 ± 0.71 after 24 - 27 days of culture. Maximum root induction (90 and 80%) was found on MS supplemented with 0.5 mg/l IBA and 0.5 mg/l NAA in case of BARI Ada-1 and Chinese ginger, respectively. The in vitro regenerated plantlets were successfully transplanted into the soil after acclimatization.